Characteristics and formative mechanism of lacustrine deep-water gravity flow deposition: a case study of the Yanchang Formation in the Ordos Basin - Taping He; Wenju Wang; Xiaobin Xie; Ke Li; Qing Deng; Shuxian Li; Zhenwei Zhang; Zhou Yaoqi (Journal of Petroleum Exploration and Production Technology)
Abstract The sedimentary mechanisms and depositional processes of deep-water gravity flows in lacustrine basins remain incompletely understood, posing challenges for accurate reservoir prediction in continental rift basins. This study investigates the Triassic Yanchang Formation in the Ordos Basin to elucidate the genetic processes and evolutionary mechanisms of deep-lake gravity flow deposits. Through systematic core observations, grain size analysis (including mean size, sorting, skewness and kurtosis), and sedimentary facies analysis, we identified four distinct gravity flow types: (1) sandy debris flows, (2) muddy debris flows, (3) turbidity currents, and (4) slumps. Quantitative grain size parameters reveal significant differences among these facies, with mean grain size ranging from 1.19Φ to 3.53Φ. Three primary triggering mechanisms are recognized: seismic events (seismites), volcanic events (tuffaceous layers), and anoxic events ("Zhangjiatan" shales), with seismic and volcanic events exerting particularly strong influences. A new depositional pattern is proposed, detailing the complete evolutionary sequence from slope failure initiation to final deposition, encompassing the sliding-slumping-debris flow-turbidity current transition. This study advances understanding by: (1) establishing quantitative discriminators for different gravity flow types, (2) clarifying the causal relationships between external triggers and flow deposition, and (3) providing a comprehensive evolutionary framework for lacustrine gravity flow systems. These findings significantly enhance the ability to predict deep-lacustrine sedimentary architectures and hydrocarbon reservoirs, offering valuable insights for exploration in analogous rift basins.